2013
DOI: 10.5194/hessd-10-10461-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modelling pesticide leaching under climate change: parameter vs. climate input uncertainty

Abstract: The assessment of climate change impacts on the risk for pesticide leaching needs careful consideration of different sources of uncertainty. We investigated the uncertainty related to climate scenario input and its importance relative to parameter uncertainty of the pesticide leaching model. The pesticide fate model MACRO was calibrated against a comprehensive one-year field data set for a well-structured clay soil in south-west Sweden. We obtained an ensemble of 56 acceptable parameter sets that repres… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…In fact, quantification of this model uncertainty has been investigated extensively in recent years for several different hydrologic models (Chen et al, 2011b;Poulin et al, 2011;Steffens et al, 2014). These studies suggest that multiple hydrologic models with multiple calibration sets should be considered when making management decisions.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, quantification of this model uncertainty has been investigated extensively in recent years for several different hydrologic models (Chen et al, 2011b;Poulin et al, 2011;Steffens et al, 2014). These studies suggest that multiple hydrologic models with multiple calibration sets should be considered when making management decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Fowler et al, 2007). We followed the approach and reasoning described in Steffens et al (2014). The change factors were derived by comparing the projected present and future climate periods for each member of the ensemble of climate scenarios.…”
Section: Study Regionmentioning
confidence: 99%
“…Most of these studies only considered the potential direct impacts of climate change. Bloomfield et al (2006), Beulke et al (2007), as well as Steffens et al (2013Steffens et al ( , 2014 hypothesized that the indirect effects of climate change might be more significant for future pesticide losses than direct effects, but to our knowledge only a few studies have explicitly attempted to quantify such effects. Kattwinkel et al (2011) assessed the effects of climate change on the exposure of surface water to agricultural insecticides and concluded that the combined effect is likely to be stronger than the direct or indirect effects of climate change (i.e.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Soil retentive processes and biodegradation kinetics are key parameters in predicting offsite transport of herbicides [1,2]. Sorptive and physical entrapment processes interact with highly compartmentalized tortuous pore space to impose limitations on the availability of herbicides to the plants they are designed to kill, as well as the microorganisms required for biodegradation [3,4].…”
mentioning
confidence: 99%